A SERM increasing the expression of the osteoblastogenesis and mineralization-related proteins and improving quality of bone tissue in an experimental model of osteoporosis - Yogui, Fernanda Costa [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; Faverani, Leonardo Perez [UNESP]; Polo, Tarik Ocon Braga [UNESP]; Ramalho-Ferreira, Gabriel [UNESP]; Hassumi, Jaqueline Suemi [UNESP]; Rossi, Ana Cláudia; Freire, Alexandre Rodrigues; Prado, Felippe Bevilacqua; Okamoto, Roberta [UNESP] (FapUNIFESP (SciELO), 2018)
Raloxifene is an antiresorptive drug, selective estrogen receptor modulator (SERM) used in the treatment of osteoporosis. Objective: To evaluate proteins related to bone repair at the peri-implant bone in a rat model of osteoporosis treated with raloxifene. Material and Methods: 72 rats were divided into three groups: SHAM (healthy animals), OVX (ovariectomized animals), and RLX (ovariectomized animals treated with raloxifene). Raloxifene was administered by gavage (1 mg/kg/day). Tibial implantation was performed 30 days after ovariectomy, and animals were euthanized at 14, 42, and 60 days postoperatively. Samples were collected and analyzed by immunohistochemical reactions, molecular analysis, and microtomographic parameters. Results: RLX showed intense staining of all investigated proteins at both time points except for RUNX2. These results were similar to SHAM and opposite to OVX, showing mild staining. The PCR gene expression of OC and ALP values for RLX (P<0.05) followed by SHAM and OVX groups. For BSP data, the highest expression was observed in the RLX groups and the lowest expression was observed in the OVX groups (P<0.05). For RUNX2 data, RLX and SHAM groups showed greater values compared to OVX (P<0.05). At 60 days postoperatively, microtomography parameters, related to closed porosity, showed higher values for (Po.N), (Po.V), and (Po) in RLX and SHAM groups, whereas OVX groups showed lower results (P<0.05); (BV) values (P=0.009); regarding total porosity (Po.tot), RLX group had statistically significant lower values than OVX and SHAM groups (P=0.009). Regarding the open porosity (Po.V and Po), the SHAM group presented the highest values, followed by OVX and RLX groups (P<0.05). The Structural Model Index (SMI), RLX group showed a value closer to zero than SHAM group (P<0.05). Conclusions: Raloxifene had a positive effect on the expression of osteoblastogenesis/mineralization-related proteins and on micro-CT parameters related to peri-implant bone healing.
Keywords: Dental implants; Immunohistochemistry; Osteoporosis; Raloxifene; WNT signaling